Pengaruh Penerapan Terapi Komplementer Akupreasure Titik P6 Terhadap Penurunan Skala Mual Pada Ibu Hamil Primigravida Trimester I - Sri Ayu; Sobar Darmaja; Wiwin Nur Fitriani (Politeknik Karya Husada, 2025)
Background: Emesis gravidarum is a multifactorial condition influenced by hormonal changes, predisposing factors(parity, age, occupation, nutrition, psychological factors, social support, and obesity), and anxiety. Acupressure on thePericardium 6 (P6) point is a nonpharmacological therapy that can inhibit the vomiting center through the release ofbeta-endorphins.Objective: To analyze the relationship between preconception anxiety and pregnancy-related nausea and vomiting, aswell as the effect of acupressure on the Pericardium 6 (P6) point on reducing nausea scores in primigravid women intheir first trimester in Ridogalih Village in 2024.Methods: This quasi-experimental study with a non-equivalent control group design involved 30 primigravid women intheir first trimester, selected using total sampling. Data analysis utilized the Chi-Square test and the Wilcoxon Signed-Rank test.Results: There was a significant association between preconception anxiety and the incidence of nausea in both the casegroup (p=0.037) and the control group (p=0.006). The P6 acupressure intervention had a significant effect on reducingnausea scores in the case group (p=0.000), but not in the control group (p=0.564).Conclusion: P6 acupressure is effective in reducing nausea complaints in primigravida women in the first trimester andis recommended as a self-administered nonpharmacological therapy.